2007
DOI: 10.1177/0011128707309718
|View full text |Cite
|
Sign up to set email alerts
|

Minority Threat, Crime Control, and Police Resource Allocation in the Southwestern United States

Abstract: Numerous studies have examined political influences on communities' allocations of fiscal and personnel resources to policing. Rational choice theory maintains that these resources are distributed in accordance with the need for crime control, whereas conflict theory argues that they are allocated with the aim of controlling racial and ethnic minorities. Existing research more consistently supports the conflict argument, but important issues remain unaddressed. The authors tested that approach by examining all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 41 publications
4
90
0
Order By: Relevance
“…This research suggests that support for increases in criminal justice expenditures varies by the minority group being examined. Holmes et al [16] find that percentage of Hispanics has a minimal influence on resource allocation as compared to percentage of Blacks. While percent Black has a strong, positive association with police resource allocation, percent Hispanic had a weak, positive relationship.…”
Section: Police Expendituresmentioning
confidence: 99%
“…This research suggests that support for increases in criminal justice expenditures varies by the minority group being examined. Holmes et al [16] find that percentage of Hispanics has a minimal influence on resource allocation as compared to percentage of Blacks. While percent Black has a strong, positive association with police resource allocation, percent Hispanic had a weak, positive relationship.…”
Section: Police Expendituresmentioning
confidence: 99%
“…For example, most of it has sampled university students, and it has generally ignored the possibility that Whites may recognize different ethnicities among Hispanics (e.g., Cubans, Columbians, Mexicans, Chicanos, Puerto Ricans; see Marin 1984;Martinez and Valenzuela 2006), which our research also fails to do. However, the extant literature indicates that: (1) Whites have constructed gendered negative stereotypes of Hispanics, (2) that they have deep historical roots, and (3) that these stereotypes include depictions of Hispanic men as being violent (Bender 2003;Castro 2006;Hagan and Palloni 1999;Holmes et al 2008;Martinez and Valenzuela 2006;Portillos 2006;Samora 1971). Marin (1984) used a free-response question format and found that the primary characteristic assigned to all Hispanic groups by 100 college students of different races and ethnicities was ''aggressive''; 64 percent of the respondents assigned this attribute to ''Chicanos.'…”
Section: Stereotypes Of Hispanics As Being Violentmentioning
confidence: 99%
“…Given the highly visible pattern of Latino immigration in combination with criminal stereotypes (e.g. Holmes et al, 2008), it stands to reason that it would take fewer resident whites to mount a threat response in reply to Latino encroachment.…”
mentioning
confidence: 99%